The behaviour of managers in Austria and the czech Republic: An intercultural comparison based on the Vroom/Yetton Model of leadership and decision making - Gerhard Reber; Werner Auer-Rizzi; Milan Malý (Journal for East European Management Studies, 2004)
In this paper we compare the leadership behaviour of managers in Austria and the Czech Republic, employing the Vroom/Yetton situational leadership model. The model applies a methodology that is close-to-action in contrast to the collection of empirical data based on questionnaires, which target the revelation of basic values as determinants of intercultural differences (farfrom- action), such as the studies of Hofstede and the GLOBE-Project. The results show that leadership behaviour in the Czech Republic remains autocratic despite dramatic changes in the societal and political environment of the two countries. – – In diesem Aufsatz vergleichen wir das Führungsverhalten von Managern in Österreich und der Tschechischen Republik anhand des Vroom/Yetton situationsbezogenen Führungsmodells. Das Modell nutzt eine Methodik, die praktisch ist im Vergleich zur Sammlung von empirischen Daten, die auf Fragebögen basieren und welche die Enthüllung von Grundwerten als Determinanten von interkulturellen Unterschieden (theoretisch) wie die Studien von Hofstede und das GLOBE-Projekt zum Ziel hat. Die Ergebnisse zeigen, dass dass Führungsverhalten in der Tschechischen Republik immer noch autokratisch ist, trotz dramatischer Veränderungen sowohl im sozialen als auch im politschen Umfeld in beiden Ländern.
Keywords: 650; Leadership behaviour; participation; Czech Republic; Austria; cross cultural studies